Thymoquinone regulates gene expression levels in morphine addiction pathways in opioid receptor expressing cells (U87 MG) - Nasir, Mohamad; Chieng, Yeo Chew; Khairi, Che Mat; Rusli, Ismail (2017)
Background: New drugs are continuously being developed for the treatment of opioid dependence individuals. Thymoquinone is one of the drugs that exhibits inhibitory characteristics based on in vivo and in vitro models. Aim: This study further investigates the effects of thymoquinone on human global gene expression from opioid receptor expressing cell line (OREC) using RNA sequencing technology. The cell line that we used was human monoglioma cancer cells (U87 MG). Method: The quantification of RNA samples was carried out using an Agilent 2100 Bioanalyser to determine the RNA integrity number (RIN). Samples with RIN>9.4 were used for further analysis. The universal human reference RNA was used as the common reference. The samples were treated with morphine alone (35 µM), morphine with methadone (162 µM), morphine with methadone and TQ (61 μM) and morphine with TQ for 48 h. The control cells were treated with an equivalent volume of vehicle in growth media. Total RNA was isolated from the U87 MG cells using the RNA mini kit’s protocol (Geneaid) and quantified using a BioDrop 2000c spectrophotometer. After mRNA enrichment and cDNA synthesis, the amplified cDNA fragments were paired-end sequencing using Illumina sequencing system with 2*150 sequencing method and subjected to subsequent bioinformatics analysis. Findings: The results showed that thymoquinone upregulated phosphodiesterase 1 A (PDE1A) genes, gamma-aminobutyric acid type A receptor theta subunit (GABRQ) and G protein subunit beta 3 (GNG3) genes in which these genes were down regulated by the chronic morphine. Conclusion: These findings indicate that thymquinone targets specific genes in morphine addiction pathways.